Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1002/bjs.10794
|View full text |Cite
|
Sign up to set email alerts
|

Routine histopathological examination after female-to-male gender-confirming mastectomy

Abstract: The discovery of an unexpected breast cancer in a 31-year-old transman emphasizes the importance of thorough routine histopathological examination of mastectomy specimens. The number of tissue blocks taken should be based on age and breast weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 21 publications
1
40
0
1
Order By: Relevance
“…2 The reported incidence of atypical/significant findings has ranged from 1.5% to 4.7%. [2][3][4][5] Atypical breast lesions were identified in our investigation at a rate of 2.8% (6 of 211) in the transmasculine cohort, which falls within the reported range of 1.5% to 4.7%. Resection of clinically benign RM specimens returned the diagnosis of atypia or carcinoma in our study with a rate of 5.5% (14 of 252 patients) and 24% (5 of 21 patients) undergoing bilateral and unilateral balancing RM, respectively (7% overall).…”
Section: Comparative Analysis Between Gender-affirming Surgery and Rmsupporting
confidence: 77%
See 2 more Smart Citations
“…2 The reported incidence of atypical/significant findings has ranged from 1.5% to 4.7%. [2][3][4][5] Atypical breast lesions were identified in our investigation at a rate of 2.8% (6 of 211) in the transmasculine cohort, which falls within the reported range of 1.5% to 4.7%. Resection of clinically benign RM specimens returned the diagnosis of atypia or carcinoma in our study with a rate of 5.5% (14 of 252 patients) and 24% (5 of 21 patients) undergoing bilateral and unilateral balancing RM, respectively (7% overall).…”
Section: Comparative Analysis Between Gender-affirming Surgery and Rmsupporting
confidence: 77%
“…Recent investigations have shown that histologic findings are predominantly benign, including lobular atrophy and stromal fibrosis reminiscent of the fibrotic stage of gynecomastia (Table 2). [3][4][5] Similarly, a recent study compared a transmasculine cohort to women undergoing RM and showed a significantly greater proportion of benign changes including fibrous stroma, ectatic ducts, fibroadenomatous change, and calcifications in the gender-affirming group. 2 The reported incidence of atypical/significant findings has ranged from 1.5% to 4.7%.…”
Section: Comparative Analysis Between Gender-affirming Surgery and Rmmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018) [ 33 ] Case report 58 Yes, incidental finding Unknown 25 Invasive ductal carcinoma Unknown ER+, PR-, HER2- Van Renterghem et al. (2018) [ 18 ] Retrospective cohort study 31 Yes, incidental finding Negative 1.3 Moderately differentiated invasive carcinoma Unknown ER+, PR+, HER2- Fledderus et al. (2020) (current article) Case report 50 Yes, incidental finding Positive 3 DCIS Not tested Not tested No∗: suspicion for malignancy, diagnosis confirmed by histological examination after mastectomy; Yes, incidental finding: by histological analysis after mastectomy; ER: estrogen receptor; PR: progesterone receptor; HER2: Human Epidermal growth factor Receptor; AR: androgen receptor; -: negative; +: positive; DCIS: ductal carcinoma in situ.…”
Section: Resultsmentioning
confidence: 99%
“…A study with 1579 American veteran FtM transsexuals found seven FtM transsexuals with breast cancer, whereas only one was documented to use testosterone prior to diagnosis [16] . Three cohort studies including 795, 96, and 283 FtM transsexuals receiving testosterone all found one subject with breast malignancy or premalignancy in their cohort [17] , [18] , [19] . A recent Dutch study evaluated the incidence of breast cancer in the FtM transsexual population in their clinical center [20] .…”
Section: Resultsmentioning
confidence: 99%